Acquisition of orthographic knowledge: Developmental difference among learners with Chinese as a second language (CSL). (June 2018) - Loh, Elizabeth Ka Yee; Liao, Xian; Leung, Shing On
Abstract: Drawing upon existing research on acquisition of orthographic skills among Chinese learners, this research further extended the scope to investigate the developmental difference among Chinese as a second language (CSL) learners in Hong Kong. A total of 157 students, including 32 fifth graders, 44 seventh graders, 42 ninth graders and 39 eleventh graders responded to three orthographic tasks tapping knowledge on three aspects of Chinese orthography: component, structure and position regularity of component. While the constituent component and structure of characters could be perceived visually, the knowledge about position regularity of components which determines the legitimacy of characters is implicit and difficult to acquire. It was found that CSL learners demonstrated some understanding of orthographic properties of Chinese characters from Grade 5, but developed these three types of orthographic knowledge in non-synchronized ways. Moreover, it was found that structural knowledge contributed more than component knowledge to the development of position regularity knowledge. These findings suggest that teachers should place more emphasis on explicit introduction of orthographic knowledge to CSL learners and provide constructive strategies for effective learning. Highlights: This study examined the development of orthographic knowledge systematically among CSL learners. CSL learners demonstrated awareness to orthographic properties of Chinese characters during beginning stage. Structure contributed more than component to the acquisition of position regularity of components. No significant difference was found across grades in the relationship among three types of orthographic knowledge.